Applying the wellbeing valuation method to value the costs of roadworks and flooding. Issue 1 (2nd January 2022) - Fujiwara, D.; Houston, R.; Keohane, K.; Maxwell, C.; van Emmerik, I.
ABSTRACT: This study uses the wellbeing valuation method to monetise the association between water flooding or roadworks incidents and subjective wellbeing for customers served by Anglian Water in the UK. Using this method, we find that the estimated wellbeing cost per incident for flooding is considerably higher than for roadworks, that internal sewer flooding is associated with a higher wellbeing cost per property than external sewer flooding, and that internal water flooding has a lower estimated wellbeing cost per property than internal sewer flooding. The findings were used in Anglian Water's 2019 Price Review (PR19) business planning. By providing a wellbeing valuation for events that have also been studied through stated preference models, this research also provides a case study for comparing the differences in results between the two valuation methodologies.